برنامج مقترح من منظور الممارسة العامة في الخدمة الاجتماعية لتنمية مهارات القيادة الأسرية للأرامل الصغيرات - سرحان، مها عبدالودود عبدالعظيم (الجمعية العربية للتنمية البشرية والبيئية, 2023)
استهدفت تلك الدراسة تحديد مستوي مهارات القيادة الأسرية لدي الأرامل الصغيرات، تحديد المعوقات التي تحول دون اكتسابهن تلك المهارات والتوصل إلى برنامج مقترح من منظور الممارسة العامة للخدمة الاجتماعية لتنمية مهارات القيادة الأسرية للأرامل الصغيرات، وتم تطبيق تلك الدراسة على عينة قوامها (۸۸) وذلك باستخدام أسلوب الحصر الشامل مفردة بجمعية الخير للغير وجمعية منابع الخير وجمعية مصر المحروسة بلدي وتم تطبيق استمارة استبار كأداة جمع البيانات مطبقة على الأرامل الصغيرات وتوصلت نتائج تلك الدراسة إلى تدني مستوي مهارات القيادة الأسرية للأرامل الصغيرات (مهارة العلاقات الاجتماعية- مهارة حل المشكلة- المهارة التوجيهية) وتوصلت نتائج الدراسة أيضا إلى أن هناك معوقات منها تدخل أهل الزوج في شؤون الأرملة وتوصلت إلى بعض المقترحات منها تشجيع الأرملة للمشاركة في المناسبات الاجتماعية وتوصلت نتائج الدراسة إلى أن هناك ضعف في مستوي المهارات الخاصة بالأرمل الصغيرات نتيجة وجود معوقات منها تدخل أهل الزوج في شؤنها وعدم إعطائها الفرصة للاندماج في الحياة الاجتماعية وتوصلت أيضا إلى مقترحات لتنمية مهارات القيادة الأسرية للأرامل الصغيرات. This study aimed to determine the level of family leadership skills among young widows, identify the obstacles that prevent them from acquiring those skills, and come up with a proposed program from the perspective of the general practice of social service to develop the family leadership skills of young widows. This study was applied to a sample of (88) using the method A comprehensive survey of the Al-Khair Association for Others, the Manabi Al-Khair Association, and the Misr Al-Mahrousa Baladi Association. A questionnaire was applied as a data collection tool applied to young widows. The results of this study revealed a low level of family leadership skills for young widows (social relations skill- problem solving skill- guidance skill) The results of the study also found that there are obstacles, including the interference of the husband’s family in the widow’s affairs, and it came up with some suggestions, including encouraging the widow to participate in social events. Based on these results, a proposed program and recommendations for the study were developed The results of the study concluded that there is a weakness in the level of skills of young widows as a result of the presence of obstacles, including the interference of the husband’s family in her affairs and not giving her the opportunity to integrate into social life. It also reached proposals for developing the family leadership skills of young widows.
Keywords: القضايا الاجتماعية -- القيم الاسرية -- المهارات القيادية -- حقوق المرأة -- الأرامل الصغيرات